2001
DOI: 10.1081/ese-100000473
|View full text |Cite
|
Sign up to set email alerts
|

Application of Path Analysis to Urinary Findings of Cadmium-Induced Renal Dysfunction

Abstract: Thiodan (33.7% endosulfan), a polychlorinated cyclodiene insecticide, was evaluated for its histopathological effects on mosquitofish, Gambusia affinis, by light microscopy. Fish were exposed to doses of 0.00 (control), 1.00, 2.50, and 5.00 microg/L on days 7, 14, 21, and 30. No histopathological effects were apparent at control group. The histopathological alterations were characterized as oedema, degeneration, accumulation of lymphocytes in the lamina propria, disintegration of villuses, pycnotic state of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…As a result of the widespread use of Cd in industry and its extensive dissemination in the environment, much attention has been focused on the identification of urinary biomarkers of the early stages of Cd-nephrotoxicity (Abe et al, 2001; Bernard, 2004; Mueller et al, 1998; Nakajima et al, 2005; Roels et al, 1999; Shaikh and Smith, 1986). Some of the urinary biomarkers that have been used for this purpose include the Cd-binding protein metallothionein (Shaikh et al, 1990), low molecular weight proteins such as β-2 microglobulin (Lauwerys et al, 1984) and Clara cell protein-16 (CC-16) (Bernard et al, 1994), and even Cd itself (Bernard, 2004; Mueller et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the widespread use of Cd in industry and its extensive dissemination in the environment, much attention has been focused on the identification of urinary biomarkers of the early stages of Cd-nephrotoxicity (Abe et al, 2001; Bernard, 2004; Mueller et al, 1998; Nakajima et al, 2005; Roels et al, 1999; Shaikh and Smith, 1986). Some of the urinary biomarkers that have been used for this purpose include the Cd-binding protein metallothionein (Shaikh et al, 1990), low molecular weight proteins such as β-2 microglobulin (Lauwerys et al, 1984) and Clara cell protein-16 (CC-16) (Bernard et al, 1994), and even Cd itself (Bernard, 2004; Mueller et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the urinary excretion of metallothionein is a marker of Cd exposure as well as proximal tubular injury, but identifying the critical level of urinary metallothionein to indicate the onset of tubular injury has been problematic. 16,19,21,22,28,35,36 Moreover, it is not totally clear if increases in the urinary excretion of b 2 -microglobulin and CC-16 are solely markers of tubular dysfunction, or are a reflection of the blood levels of the proteins, which can be influenced by actions of toxicants on organs other than the kidney. 21 Kidney injury molecule-1 (Kim-1), which is also known as hepatitis A virus cellular receptor 1 (Havcr1), 37 is a type I transmembrane protein that is not detectable in normal kidney tissue, but is expressed at high levels in dedifferentiated proximal tubule epithelial cells after ischemic or toxic injury.…”
mentioning
confidence: 97%
“…10,16,23,31 b 2 -Microglobulin has been widely utilized in monitoring human populations for early signs of Cd-induced renal dysfunction. 16,19,32,33 Although CC-16 has not been widely used as a marker of Cd toxicity in humans, it has been used for this purpose in experimental studies in rats, where it has been shown to be comparable to b 2 -microglobulin as a marker of Cd nephrotoxicity. 34 While these markers have been used to monitor Cd toxicity in humans and experimental animals, several problems remain.…”
mentioning
confidence: 99%
See 2 more Smart Citations